Market Opportunities for Islamic Banking and Finance in Europe: A Case of Finnish Regulatory Framework - Sanaa Kadi (Journal of Islamic Economic Laws)
This article  assesses market opportunities for Islamic banking and finance (IBF) in Finland, offering an understanding of the legal environment, consumer perceptions, and potential challenges and opportunities for developing Islamic finance within the Finnish legal framework. The study employs a survey to investigate the perceptions and behaviours of Muslims towards IBF in Finland, focusing on its legal dimensions. Utilizing a mixed-methods approach, including quantitative survey data and qualitative analysis, the research aims to understand Finnish Muslims' attitudes, preferences, and experiences towards Islamic banking products and services. The findings show that although a significant proportion of respondents revealed uncertainty or lack of knowledge about IBF, most respondents express their willingness to become customers of an Islamic financial institution if such institutions were available in Finland. This research contributes to the existing body of knowledge in Islamic finance law by elucidating the legal intricacies of Islamic banking within the European context. The insights generated offer valuable implications for policymakers, legal practitioners, and scholars interested in Islamic finance law.